The law of blood : thinking and acting as a Nazi - Chapoutot, Johann 1978- (The Belknap Press of Harvard University Press, 2018)
Part I. Procreating: Origins: nature, essence, genesis -- Alienation: acculturation and denaturing -- Restoration: renaissance -- Part II. Fighting: "All life is struggle" -- The war within: fighting the Volksfremde -- The war outside: "Harshness makes the future kind" -- Part III. Reigning: The international order of Westphalia and Versailles: Finis Germaniae -- The Reich and the colonization of the European east -- The millennium as frontier